Changes in Cognitive Outcomes in Early Childhood: The Role of Family Income and Volatility - Sosu, Edward M.; Schmidt, Peter (Frontiers in Psychology, 2022)
Associations between family income and child developmental outcomes are well documented. However, family income is not static but changes over time. Although this volatility represents income shocks that are likely to affect children’s lives, very few studies have so far examined its effect on early cognitive development. This study investigated associations between family income, volatility, and changes in cognitive outcomes in early childhood, and examined whether these association are dependent on a family’s overall income position. Data for the study spanned five waves of the Growing Up in Scotland longitudinal survey (N=3,621). Findings indicate that income volatility was more prevalent among disadvantaged sociodemographic groups. In addition to average income, short-term volatility was associated with changes in child cognitive outcomes from ages 3 to 5. While upward volatility was associated with gains in expressive vocabulary, downward and fluctuating volatility were associated with declines in child problem-solving abilities. The association between volatility and changes in cognitive outcomes was similar for both children living in poverty and those from medium-high income households. Our results suggest that policies aiming to cushion all families from negative income shocks, boost family income to ensure stability, and take low-income families out of poverty will have a significant impact on children’s cognitive development. Additionally, a more nuanced conceptualization of income is needed to understand its multidimensional impact on developmental outcomes.